Patients', clinicians' and the research communities' priorities for treatment research: there is an important mismatch. Issue 1 (December 2015) - Crowe, Sally; Fenton, Mark; Hall, Matthew; Cowan, Katherine; Chalmers, Iain
Plain English summary There is some evidence that there is a mismatch between what patients and health professionals want to see researched and the research that is actually done. The James Lind Alliance (JLA) research Priority Setting Partnerships (PSPs) were created to address this mismatch. Between 2007 and 2014, JLA partnerships of patients, carers and health professionals agreed on important treatment research questions (priorities) in a range of health conditions, such as Type 1 diabetes, eczema and stroke. We were interested in how much these JLA PSP priorities were similar to treatments undergoing evaluation and research over the same time span. We identified the treatments described in all the JLA PSP research priority lists and compared these to the treatments described in a group of research studies (randomly selected) registered publically. The priorities identified by JLA PSPs emphasised the importance of non-drug treatment research, compared to the research actually being done over the same time period, which mostly involved evaluations of drugs. These findings suggest that the research community should make greater efforts to address issues of importance to users of research, such as patients and healthcare professionals. Abstract Background Comparisons of treatment research priorities identified by patients and clinicians with research actually being done by researchers are very rare. One of the best known of these comparisons (Tallon et al. Relation between agendas of the research community and the research consumer 355:2037–40, 2000) revealed important mismatches in priorities in the assessment of treatments for osteoarthritis of the knee: researchers preferenced drug trials, patients and clinicians prioritised non-drug treatments. These findings were an important stimulus in creating the James Lind Alliance (JLA). The JLA supports research Priority Setting Partnerships (PSPs) of patients, carers and clinicians, who are actively involved in all aspects of the process, to develop shared treatment research priorities. We have compared the types of treatments (interventions) prioritised for evaluation by JLA PSPs with those being studied in samples of clinical trials being done over the same period. Objective We used treatment research priorities generated by JLA PSPs to assess whether, on average, treatments prioritised by patients and clinicians differ importantly from those being studied by researchers. Methods We identified treatments mentioned in prioritised research questions generated by the first 14 JLA PSPs. We compared these treatments with those assessed in random samples of commercial and non-commercial clinical trials recruiting in the UK over the same period, which we identified using WHO's International Clinical Trials Registry Platform. Results We found marked differences between the proportions of different types of treatments proposed by patients, carers and clinicians and those currently being evaluated by researchers. In JLA PSPs, drugs accounted for only 18 % (23/126) of the treatments mentioned in priorities; in registered non-commercial trials, drugs accounted for 37 % (397/1069) of the treatments mentioned; and in registered commercial trials, drugs accounted for 86 % (689/798) of the treatments mentioned. Discussion Our findings confirm the mismatch first described by Tallon et al. 15 years ago. On average, drug trials are being preferenced by researchers, and non-drug treatments are preferred by patients, carers and clinicians. This general finding should be reflected in more specific assessments of the extent to which research is addressing priorities identified by the patient and clinician end users of research. It also suggests that the research culture is slow to change in regard to how important and relevant treatment research questions are identified and prioritised.